2016
DOI: 10.3109/09273948.2015.1100747
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinal Nerve Fiber Layer and Ganglion Cell–Inner Plexiform Layer Thickness in Children with Familial Mediterranean Fever

Abstract: It appears that FMF does not affect the RNFL and GCIPL thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…2 In our exclusion criteria, which we did mention in the article, were patients with cycloplegic refractive errors of more than ±1.00 diopters (D). Cegarra et al 3 found that there is an anatomic relationship between ocular axial length and refractive errors.…”
mentioning
confidence: 99%
“…2 In our exclusion criteria, which we did mention in the article, were patients with cycloplegic refractive errors of more than ±1.00 diopters (D). Cegarra et al 3 found that there is an anatomic relationship between ocular axial length and refractive errors.…”
mentioning
confidence: 99%
“…IL-1β and TNF-α cytokines have also been reported to cause optic neuropathy and retinal ganglion cell degeneration in certain animal studies [ 8 , 9 ]. These facts suggest that the peripapillary retinal nerve fiber layer (pRNFL) and ganglion cell-inner plexiform layer (GCIPL) thicknesses can be affected in FMF patients as reported in some studies [ 10 , 11 ]. Another study has emphasized that increased inflammation may also alter the choroidal thickness by causing vascular problems [ 12 ] Alim et al [ 13 ] have also mentioned a possible effect of oral colchicine on pRNFL, GCIPL and choroidal thickness.…”
Section: Introductionmentioning
confidence: 77%
“…Oral colchicine and FMF disease were seen to have no effect on pRNFL thickness. There is either no mention of the patients’ colchicine use in studies on pRNFL and choroid thickness measurements of FMF patients or all the OCT measurements were taken when the patients were on colchicine [ 10 12 ]. None of these studies on retinal and pRNFL thickness have reported any difference between FMF patients and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…40 Unique treatment issues, particularly the management of cataracts to minimize the risk of amblyopia 41,42 and judicious use of systemic corticosteroids to avoid growth retardation, are also encountered. 43,44 Three reviews, 34,45,46 seven original articles, [47][48][49][50][51][52][53] and two letters 54,55 in this issue of Ocular Immunology & Inflammation (OII) address important aspects of the causes, management, complications, and outcomes of uveitis in children and adolescents.…”
mentioning
confidence: 99%
“…Alim et al 47 used spectral domain-optical coherence tomography (SD-OCT) to measure the thickness of the peripapillary retinal nerve fiber layer (RNFL) and retinal ganglion cell-inner plexiform layer (GCIPL) in the eyes of 39 patients with FMF without ocular complaints, and 36 age-and gender-matched healthy control subjects. All patients were Turkish with a mean age of approximately 10 years.…”
mentioning
confidence: 99%